Narratives from the Sephardic Atlantic : blood and faith - Perelis, Ronnie (Indiana series in Sephardi and Mizrahi studies., 2016)
"Identity, family, and community unite three autobiographical texts by New World Crypto-Jews, or descendants of Jews who were forced to convert to Christianity in 17th-century Iberia and Spanish America. Ronnie Perelis presents the fascinating stories of three men who were caught within the matrix of inquisitorial persecution, expanding global trade, and the network of Crypto-Jewish activity. Each text, translated here for the first time, reflects the unique experiences of the author and illuminates their shared, deeply rooted attachment to Iberian culture, their Atlantic peregrinations, and their hunger for spiritual enlightenment. Through these writings, Perelis focuses on the social history of transatlantic travel, the economies of trade that linked Europe to the Americas, and the physical and spiritual journeys that injected broader religious and cultural concerns into this complex historical moment"--